2013
DOI: 10.1016/j.childyouth.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Examining the equivalence of fidelity over two generations of KEEP implementation: A preliminary analysis

Abstract: Problem In order to obtain and maintain positive outcomes garnered from evidence-based practice (EBP) models, it is necessary to implement them effectively in “real world” settings, to continually monitor intervention fidelity to prevent drift, and to train new staff due to turnover. The fidelity monitoring processes that are commonly employed in research settings are labor intensive and probably unrealistic to employ in community agencies given the additional burden and cost that they represent over and above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Thus, OSLC sought to build a mechanism whereby the agencies were prepared to use their own internal personnel to take over the implementation activities that initially OSLC developers conducted including the initial staff training workshop and providing ongoing fidelity monitoring and the consulting activities. Drawing on our previous experiences in creating sustainability plans for the KEEP model (Chamberlain, Price, Reid, et al, 2008), we opted to use the Cascading Dissemination model (Buchanan, Chamberlain, Price, & Sprengelmeyer, 2013). …”
Section: Logistics Of Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, OSLC sought to build a mechanism whereby the agencies were prepared to use their own internal personnel to take over the implementation activities that initially OSLC developers conducted including the initial staff training workshop and providing ongoing fidelity monitoring and the consulting activities. Drawing on our previous experiences in creating sustainability plans for the KEEP model (Chamberlain, Price, Reid, et al, 2008), we opted to use the Cascading Dissemination model (Buchanan, Chamberlain, Price, & Sprengelmeyer, 2013). …”
Section: Logistics Of Implementationmentioning
confidence: 99%
“…Fidelity is measured across three dimensions including (1) content, (2) process, and (3) structure using a standardized rating protocol (Facilitator Adherence Rating; FAR, Buchanan et al, 2013). During groups, the facilitators record each session using a laptop with software that enables the recording to be uploaded to a secure website.…”
Section: Brief Description Of the Interventionsmentioning
confidence: 99%
“…As one possible remedy, some researchers have explored the impact of various 'train the trainer" models in which indigenous agency staff are taught to provide the EBP training and/or supervision after the outside experts are gone. In their cascading implementation research described previously, Chamberlain and colleagues found that "second generation" interventionists (trained and supervised by "first generation" interventionists who had been trained by the treatment developers) achieved fidelity and client outcomes similar to those obtained by the first generation interventionists themselves (Buchanan, Chamberlain, Price & Sprengelmeyer, 2013;Chamberlain, Price, Reid, & Landsverk, 2008). Other treatment developers have had less positive experiences with train-the-trainer and second generation models, and have thus retained more prolonged involvement of the intervention developer team (see e.g., Curtis, Ronan, & Borduin, 2004;Henggeler & Schaeffer, 2010).…”
Section: Testing Specific Elements Of DImentioning
confidence: 99%
“…Fidelity to the KEEP curriculum is monitored closely and is measured across three dimensions including: (1) content, (2) process, and (3) structure, using a standardized rating protocol (Facilitator Adherence Rating; FAR; Buchanan, Chamberlain, Price, & Sprengelmeyer, 2013). During groups, the facilitators record each session using a laptop with software that enables the recording to be uploaded to a HIPAA-compliant, secure website designed to allow for direct observation of group sessions (Fidelity Observation System; FIDO).…”
Section: Description Of the Interventionsmentioning
confidence: 99%